Disaster Prevention Management for Landslide Risk Reduction: A Qualitative Study in Purbalingga Regency, Indonesia - Marzuki; Rafi Naufal Aryanto (Yayasan Hisnul Muslim Lombok, 2025)
Landslides represent a major disaster risk in many regions of Indonesia, requiring effective disaster prevention management at the local government level. This study aims to examine disaster prevention management for landslide risk reduction in Purbalingga Regency, Central Java, Indonesia, using George R. Terry’s management framework as an analytical lens. A qualitative descriptive approach was employed, with data collected through in-depth interviews, field observations, and document analysis involving local government officials and community representatives in landslide-prone areas. The findings indicate that disaster prevention management has been implemented through planning, organizing, actuating, and controlling functions. Planning activities include hazard identification and risk mapping, while organizing focuses on institutional coordination led by the Regional Disaster Management Agency. Actuating is reflected in community awareness programs and preventive actions, although community participation remains uneven. Controlling functions are primarily administrative, with limited outcome-based evaluation. The discussion reveals that while the basic structure of disaster prevention management exists, its effectiveness is constrained by limited institutional capacity, resource availability, and weak monitoring mechanisms. This study contributes to disaster governance literature by demonstrating the applicability of classical management theory to disaster prevention in a local government context. The findings provide practical insights for strengthening managerial capacity and improving landslide risk reduction strategies in disaster-prone regions of developing countries.